A Comparative Study on Aflatoxin B(1) Metabolism in Mice and Rats - Steyn, M. (Nature Publishing Group, 1971)
In vivo metabolic studies on rats and mice revealed a marked difference in the fluorescent compounds produced after ingestion of aflatoxin B(1). The mouse converted aflatoxin B(1) to three unknown fluorescent compounds, designated x(1), x(2) and x(3) and the known aflatoxin M(1), while the rat was only capable of producing aflatoxin M(1). The results suggested that metabolites x(1), x(2), x(3) and aflatoxin M(1) were not part of a major metabolic pathway, but produced independently. These unknown yellowish-green fluorescent compounds did not seem to be conjugated with sulphate or glucuronic acid. In vitro incubations of various mouse liver cell fractions with aflatoxin B(1) showed that metabolites x(1), x(2), x(3) and aflatoxin M(1), could only be produced by the microsomal fraction and that NADPH was needed as a co-factor. The differences in aflatoxin metabolism by mice and rats are discussed in relation to the apparent resistance of the mouse to the carcinogenic effects of this toxin.